Exploring the mycobiome and arbuscular mycorrhizal fungi associated with the rizosphere of the genus Inga in the pristine Ecuadorian Amazon - Arévalo-Granda, Valentina; Hickey-Darquea, Aileen; Prado-Vivar, Belén; Zapata, Sonia; Duchicela, Jéssica; van ‘t Hof, Pieter (Frontiers in Fungal Biology, 2023)
This study explored the composition of the mycobiome in the rhizosphere of Inga seedlings in two different but neighboring forest ecosystems in the undisturbed tropical Amazon rainforest at the Tiputini Biodiversity Station in Ecuador. In terra firme plots, which were situated higher up and therefore typically outside of the influence of river floods, and in várzea plots, the lower part of the forest located near the riverbanks and therefore seasonally flooded, tree seedlings of the genus Inga were randomly collected and measured, and the rhizosphere soils surrounding the root systems was collected. Members of the Fabaceae family and the genus Inga were highly abundant in both forest ecosystems. Inga sp. seedlings collected in terra firme showed a lower shoot to root ratio compared to seedlings that were collected in várzea, suggesting that Inga seedlings which germinated in várzea soils could invest more resources in vegetative growth with shorter roots. Results of the physical-chemical properties of soil samples indicated higher proportions of N, Mo, and V in terra firme soils, whereas várzea soils present higher concentrations of all other macro- and micronutrients, which confirmed the nutrient deposition effect of seasonal flooding by the nearby river. ITS metabarcoding was used to explore the mycobiome associated with roots of the genus Inga. Bioinformatic analysis was performed using Qiime 2 to calculate the alpha and beta diversity, species taxonomy and the differential abundance of fungi and arbuscular mycorrhizal fungi. The fungal community represented 75% of the total ITS ASVs, and although present in all samples, the subphylum Glomeromycotina represented 1.42% of all ITS ASVs with annotations to 13 distinct families, including Glomeraceae (72,23%), Gigasporaceae (0,57%), Acaulosporaceae (0,49%). AMF spores of these three AMF families were morphologically identified by microscopy. Results of this study indicate that AMF surround the rhizosphere of Inga seedlings in relatively low proportions compared to other fungal groups but present in both terra firme and várzea Neotropical ecosystems.